HUBUNGAN TINGKAT STRES DALAM MENGHADAPI OBJECTIVE STRUCTURED CLINICAL EXAMINATION (OSCE) DENGAN KUALITAS TIDUR PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - PICA NADHRAH SARI; DEBBY MIRANI (LP2MTBM MAKARIOZ, 2021)
Medical students are potentially for having sleep disturbances because of the academic processes were associated withhigh stress levels such as Objective Structured Clinical Examination (OSCE). The high level of stress, that exceedsindividual endurance, it will cause negative impacts such as difficulty concentrating, headache, difficulty to sleeping.This research is descriptive analytic study with cross-sectional approach. Sampling was done by consecutive samplingtechnique and has obtained a sample of 146 respondents. Data were analyzed using Chi Square test. Chi-square test resultshowed that there was significant result between stress level during OSCE with sleep quality among medical student with avalue of p = 0,003 (p<0,05). There is a relationship between stress level during OSCE with sleep quality among medicalstudent at faculty of medicine, muhammadiyah university of north sumatera.